Nursing performance in robotic surgeries: integrative review - Raísha Costa Martins; Denilse Damasceno Trevilato; Marielli Trevisan Jost; Rita Catalina Aquino Caregnato (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To know the scientific production on the performance of the nursing staff in robotic surgeries, identifying the role of the nurse in the three perioperative periods. Methods: Integrative review, search in the databases National Library of Medicine, National Institutes of Health, Scientific Electronic Library Online and Biblioteca Virtual em Saúde, performed from June to September, 2017; 17 selected articles met the inclusion criteria. Results: Most articles were published in foreign journals in English, nine in the United States, classified with evidence level of 4 and 5. The role of nursing in the perioperative period was identified, related mainly to patient safety. The most mentioned perioperative period in the articles was the intraoperative, with greater concern in the positioning of the patient. Conclusion: The nursing performance and patient safety in robotic surgeries are similar to the ones in major surgeries, requiring from the patient a specific knowledge on the setting and preparation of the robot.